Factors that influence social media interaction among university students: emotional and mental well-being - Nur Anis Mohd Jasmi; Fauziah Redzuan; Jasber Kaur Gian Singh (Institute of Advanced Engineering and Science, 2026)
Social media usage is becoming popular among students, which is used both for academic and entertainment. However, the excessive use of social media can increase the level of stress, anxiety, and depression. The social media interaction can also lead the students to compare themselves with influencers. This study aims to identify the factors and the significant relationship between the factors of social media interaction and emotional and mental well-being. This research used a quantitative research and hypothesis-driven approach. The existing theories, such as social capital theory and social comparison theory were adapted for the online survey questionnaires. The collected data were analysed using partial least square-structural equation modelling (PLS-SEM) to analyse the two objectives of this research. Based on the findings, twelve (12) constructs were identified as the factors that contribute to social media interaction on university students' emotional and mental well-being by assessing and validating the constructs using PLS-SEM. Then, there are thirteen (13) out of twenty-three (23) hypothesis were significant relationships based on the final model testing using PLS-SEM bootstrapping method. Ten (10) paths of direct effect, two (2) paths of mediating analysis, and one (1) path of moderating analysis were significant relationships and supported the alternative hypothesis. It is recommended for future studies to also explore other analysis techniques, theories, or models, and the changes to other group such as older generations or working adults.